Pertanggung Jawaban Pihak Kepolisian dan Upaya Hukum yang Dilakukan Tersangka atas Terjadinya Salah Tangkap - I Gede Banyu Bagastya Nida; A.A Sagung Laksmi Dewi; I Made Budiyasa (Warmadewa Press, 2020)
The criminal justice system is obliged, namely to carry out detailed examinations, prioritize evidence and facts that are strong enough to determine that a person is guilty in criminal matters, and is able to carry out convictions with a purpose that is in accordance with the crime itself and the rights that should be accepted by the convicted person. This research is a normative legal research, so the research focus is on library research. The objectives of this study are: to know the responsibility of the police if there is a wrong arrest and to know the legal remedies that the suspect can take if a wrong arrest occurs. The results of the research show how Police Investigators are held accountable for irregularities in carrying out their duties and legal remedies that can be taken by the suspect in the event of irregularities by the Police Investigator. First, the forms of sanctions contained in the Code of Ethics for the Indonesian National Police if they are violated are as follows; a) Violation behavior is declared as despicable act; b) The offender's obligation to apologize in a limited or direct manner; c) The violator's obligation to follow professional reinvention; d) The offender is declared no longer entitled to carry out the police function, then legal remedies that can be taken if a violation occurs in accordance with Article 1 paragraph 22 of the Criminal Procedure Code, compensation. The legal basis for the claim for compensation is article 77 letter b KUHAP, then rehabilitation according to article 1 paragraph 10 KUHAP point c. From this research it can be concluded that the form of accountability carried out by the Police investigators is divided into 2, namely material accountability, namely the sanction of forgiveness and immaterial accountability, namely about sanctions in the form of mandatory recovery at the Polri educational institution. Meanwhile, the legal remedy that can be taken by the victim of a wrongful arrest is to file a claim for compensation and rehabilitation.